HER2 Expression in Different Types of Thyroid Neoplasms Assessed by Two Immunohistochemical Scoring Systems: A 3-Year Follow-Up Study in a Referral University Hospital in Tehran, Iran - Fahimi, Mahdieh; Mohammadi Maram, Mahsa; Kamani, Fereshteh; Mohsenifar, Zhaleh (Archives of Men's Health, 2026)
Introduction: Thyroid neoplasms are the most common endocrine malignancy; thus, it is important to introduce diagnostic and predictive factors for them. HER2, which is overexpressed in some other malignancies such as breast and gastrointestinal (GI) neoplasms, has been proposed as a diagnostic and prognostic factor. In this study, we investigated HER2 expression in different types of thyroid cancer. This study aimed to investigate the expression frequency of the human epidermal growth factor receptor 2 (HER2) in thyroid neoplasms, and its relationship with the type, stage, and prognosis of the malignancy. Material and Methods: We studied 91 patients who were referred to Taleghani Hospital, Tehran, Iran, and underwent thyroidectomy or thyroid lobectomy, in the years 2018 to 2021. Their medical records, hematoxylin and eosin (H&E)-stained slides, and paraffin-embedded blocks were extracted from the hospital pathology archive. The specimens underwent microtomy and were subjected to immunohistochemistry (IHC) for HER2 evaluation. After the interpretation, the data were statistically analyzed. Results: The only significant relationship was between HER2 expression (when interpreted based on the gastric scoring system) and age (P-value= 0.036). However, there was no significant relationship between HER2 expression and any of the other variables of our study. Conclusion: Despite HER2 being a prognostic factor in breast and GI neoplasms, our study suggests that HER2 expression has no such role in thyroid neoplasm cases, and is only positive in patients younger than 45 years old with thyroid malignancies (when interpreted based on the gastric scoring system).